2016
DOI: 10.1212/wnl.0000000000002576
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid negativity in patients with clinically diagnosed Alzheimer disease and MCI

Abstract: Objective: To examine the clinical and biomarker characteristics of patients with amyloid-negative Alzheimer disease (AD) and mild cognitive impairment (MCI) from the Alzheimer's Disease Neuroimaging Initiative (ADNI), a prospective cohort study. Methods:We first investigated the reliability of florbetapir2 PET in patients with AD and patients with MCI using CSF-Ab 1-42 as a comparison amyloid measurement. We then compared florbetapir2 vs florbetapir1 patients with respect to several AD-specific biomarkers, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 43 publications
10
76
0
3
Order By: Relevance
“…When directly comparing Aβpos to Aβneg aMCI patients, we did not find any significant difference in terms of atrophy or hypometabolism using both ROI and voxel‐based analyses. Previous studies reported inconsistent findings with some showing greater atrophy [12–14,21] or hypometabolism in Aβpos aMCI [13–15], while other studies reported same degree of brain alterations between these two groups of patients [11,22]. Similarly, it has been shown that hippocampal volume was not able to predict brain amyloidosis in aMCI (AUC = 0.56; P > .05; [46]).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When directly comparing Aβpos to Aβneg aMCI patients, we did not find any significant difference in terms of atrophy or hypometabolism using both ROI and voxel‐based analyses. Previous studies reported inconsistent findings with some showing greater atrophy [12–14,21] or hypometabolism in Aβpos aMCI [13–15], while other studies reported same degree of brain alterations between these two groups of patients [11,22]. Similarly, it has been shown that hippocampal volume was not able to predict brain amyloidosis in aMCI (AUC = 0.56; P > .05; [46]).…”
Section: Discussionmentioning
confidence: 91%
“…Landau et al. 's study [13] is the only previous study providing an overall picture of the profiles of neuropsychological changes, brain atrophy, and brain hypometabolism in Aβpos versus Aβneg aMCI patients. They reported higher hippocampal atrophy and temporoparietal hypometabolism in Aβpos compared to Aβneg aMCI.…”
Section: Introductionmentioning
confidence: 99%
“…The definitive diagnosis of AD requires information related to both of two pathological disease hallmarks, amyloid plaques and neurofibrillary tangles [37]. Additionally, some patients with other dementias may scan positive [38] and some (albeit few) patients with AD may scan negative [39]. Therefore, clinicians must be careful to appropriately set expectations for the degree of diagnostic confidence they will have when incorporating amyloid PET information into their workup.…”
Section: Discussionmentioning
confidence: 99%
“…Such individuals could be at a preclinical stage of AD, a stage of the disease that seems to be gaining clinical acceptance 15 . Around one quarter of cognitively healthy elderly people or people with mild cognitive impairment have pathological levels of tau in their brains in the absence of amyloid-β, a condition called suspected non-AD pathophysiology (SNAP) 16, 17 . Most such individuals do not express the apolipoprotein ε4 (APOE4) isoform, which is consistent with the observation that APOE4 promotes the accumulation of amyloid-β and that the APOE locus is linked to longevity.…”
Section: Overlap Between Aging and Neurodegenerationmentioning
confidence: 99%